Transcriptomic and metabolomic profiling of the potato plant response to zebra chip disease - Margaret A. Carpenter; Tonya J. Frew; Helen L. Boldingh; Simona Nardozza; Martin L. Shaw; Susan J. Thomson; Rebecca D. Cooper; Gail M. Timmerman-Vaughan (PLoS ONE, 2025)
Zebra chip disease of potato is caused by a bacterial pathogen, ‘Candidatus Liberibacter solanacearum’, vectored by the tomato potato psyllid (Bactericera cockerelli Sulc.). The plant response to the disease was explored using a combined transcriptomic and metabolomic approach. The effects of the disease were greater in tuber than in leaf or stem tissues, and represent a massive reprogramming of the tuber metabolism, with expression changes observed for many genes. In the tuber, starch synthesis was severely disrupted, with reduced expression of most starch synthesis genes, but increased expression of the gene encoding vacuolar invertase. This was consistent with increased glucose and fructose and reduced starch in the tuber, which are the hallmarks of the disease and the causes of the symptoms problematic to the potato industry. The phenylpropanoid pathway was more active in diseased tubers, as shown by increased transcript accumulation for phenylalanine ammonia lyase, cinnamate-4-hydroxylase, 4-coumarate:CoA ligase and cinnamyl alcohol dehydrogenase, and increased quantities of hydroxycinnamic acid amides, phenolic acids and coumarins. The expression of several genes encoding patatin storage proteins in the tuber was also decreased. In addition to the carbohydrate changes which cause undesirable visual symptoms associated with frying, the diseased tubers showed detrimental changes in nutritional value, such as increased toxic glycoalkaloids and decreased ascorbic acid.